Participatory Action Research on Health Evaluation and Health Problem Management for Adults in the Urban workplaces: A Case Study of Wangkanai Group - การุณงามพรรณ, มงคล; พุ่มสุทัศน์, ผกาวลี; สุวารี, สุดารัตน์; น้ำฝน, นันทนา; พิทักษ์เสถียรกุล, ชัชฎาพร (Princess of Naradhiwas University Journal, 2018)
The objective of this research was to encourage the participation of health problem evaluation and management for adults in the urban workplaces. The research tools comprised of the demographic record forms, the diabetes risk assessment form in the next 12 years with the sensitivity of 76.50 % and the specificity of 60.20 %, the health diaries, tape recorders, guideline questionnaires of heath behavior and health assessment instruments, which were prepared and verified compliance by the public health center. The 20 employees of Wangkanai group with the risk of non-communicable disease were purposive sampling. The research was conducted during November 2013 – January 2014. The process of research was composed of 1) planning 2) acting 3) observing and 4) reflecting and re-planning. The researchers collected data regarding research participants’ health data before starting the project, after joining the program for one month respectively. After the participants were informed of the results of health changes at the end of the month, the participants had visited a nutritionist, a fitness expert and the researchers to receive individual feedbacks and to have an interview on the result of changing health status. Demographic data and health status data before starting the project were analyzed using basic statistics. Health status data after joining the program for one month were classified by individual and the qualitative data were analyzed by content analysis. The results of this study revealed that four-step participatory action research of participants starting from the planning stage, participants were involved in the choice of how they performed, how they evaluated their own practice, tools that helped in monitoring behavioral health behaviors including information on exercise and eating from the experts. In acting stage, after perceiving their health status information, participants inspired, identified goals, and made behavioral modification plan. Then participants modified health behaviors under inspiration, goals, and cooperation plan among researchers, participants, and experts enhancing individual context of practice leading to good trend of health documentary in one month. Additionally, after one month, the participants were aware of the changes in health status, reflecting on the barriers, supportive factors to improve the behavioral modification plan to be implemented in the next phase to lead to success. The researchers suggested that the success of enhancement of participation of health problem management, being contributed to the change of health behaviors, depends on the unique personal plan and the participation willingness of the health owners. The participants should be provided counseling and reflection to understand the various aspects of information.